The protective role of lutein on isoproterenol-induced cardiac failure rat model through improving cardiac morphology, antioxidant status via positively regulating Nrf2/HO-1 signalling pathway - Bo Ouyang (Taylor & Francis Group, 2019)
Context: Lutein (LU) is a major carotenoid with various pharmacological activities including anti-inflammatory, antioxidant and anti-apoptosis. Objective: The cardioprotective efficacy of LU was determined by evaluating the biochemical and histopathological changes in isoproterenol (ISO) induced myocardial infarction (MI) rat model. Materials and methods: Healthy male albino rats (n = 40) were segregated into 4 equal groups. Group I (control) rats were administered with olive oil, Group II (LU) rats were orally pre-treated with only 40 mg of LU for 28 days, Group III (MI induced) rats were injected (subcutaneously; s.c) with 85 mg/kg of ISO for 2 consecutive days, whereas Group IV (LU + ISO) rats were pre-treated with 40 mg of LU for 28 days before ISO induction. Results: ISO-induced group showed increased infarct size and cardiac/inflammatory/apoptotic markers. However, pre-treatment with LU (28 days) considerably reduced (p < 0.01) the infarct size (14%), lipid peroxidation product (MDA;42%), cardiac markers [(lactate dehydrogenase (LDH) and creatine kinase-MB (CK-MB), cardiac troponin T (cTn T)], inflammatory markers [IL-1β, IL-6, tumour necrosis factor alpha (TNF-α), nuclear factor kappa B p65 subunit (NF-κB p65)] and apoptotic markers (caspase-3 and -9). Also, LU significantly improved (p < 0.01) the antioxidants [catalase (CAT), superoxide dismutase (SOD)] as well as markedly upregulated (p < 0.01) the protein expression of HO-1 and Nrf2. Moreover, LU considerably reversed all the histopathological changes and thus exhibits its cardioprotective activity. Conclusion: LU exhibits potent cardioprotective activity against ISO-induced cardiotoxicity and might be recommended with standard cardioprotective agents for treating various MI-related complications.